Saved from sacrifice: a theology of the cross - Heim, S. Mark (William B. Eerdmans Publishing Company, 2006)
The cross has long been not only a scandal but also a profound paradox: filled with saving significance and power, it is at the same time a sobering tragedy. In "Saved from Sacrifice", theologian Mark Heim takes on this paradox, asserting that the cross must be understood against the whole history of human scapegoating violence. In order to highlight the dimensions of his argument, Heim carefully and critically draws on the groundbreaking work of French theorist and biblical scholar Rene Girard. Yet, Heim goes beyond Girard to develop a comprehensive theology of the atonement and the cross through his fresh readings of well-known biblical passages and his exploration of the place of the victim.